ANALISIS PENGEMBANGAN PRIBADI KONSELOR SEBAGAI UPAYA MENINGKATKAN PROFESIONALITAS GURU BK PADA LAYANAN KONSELING DI SEKOLAH: STUDI KUALITATIF - Nengsi; Nurlaila Syipa Unnupus; Baiq Mahyatun; Hanin Ulya; Denda Wanda Ariani; Hesya Fadila Imtiyaz; Rini Sugiartini; Anisa Sapira; Imam Nawawi Zain (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The professionalism of Guidance and Counseling (GC) teachers faces various challenges due to rapid technological advancements, the diversity of students’ characteristics, and the increasing complexity of social issues within the school environment. These conditions require Guidance and Counseling teachers to possess not only academic competencies and technical counseling skills but also strong personal qualities that support the delivery of professional counseling services. This study aimed to analyze counselors’ personal development as an effort to enhance the professionalism of Guidance and Counseling teachers in school counseling services. A qualitative descriptive approach was employed, involving seven Guidance and Counseling teachers at SMA Negeri 1 Sikur as the primary participants. Data were collected through in-depth interviews, observations, and documentation and were analyzed using data reduction, data display, and conclusion drawing. The findings revealed that counselors’ personal development was fostered through strengthening personal competencies, interpersonal communication, self-reflection, lifelong learning, digital literacy, professional collaboration, and the internalization of professional ethical values. These efforts contributed to establishing effective counseling relationships, enhancing students’ trust, strengthening problem-solving abilities, and optimizing counseling services based on students’ needs. The findings indicate that counselors’ personal development is an effective strategy for enhancing the professionalism of Guidance and Counseling teachers, thereby enabling counseling services to become more adaptive, professional, and responsive to students’ needs.